PENGEMBANGAN INSTRUMEN TES LITERASI SAINS BERBASIS PISA PADA ASPEK MENJELASKAN FENOMENA ILMIAH UNTUK SISWA KELAS VII - Septiani, Dwi; Widiyawati, Yeni; Nurwahidah, Indri (Science Education and Application Journal, 2019)
This study aims to: (1) examine the quality of instruments based on PISA domain's scientific literacy in explaining scientific phenomena in the aspects of logical validity, (2) understanding empirical validity based on the VII grade science material development results, (3) knowing the level of scientific literacy of students of SMP N 3 Blora This research is a research and development (R&D) research using the Thiagarajan development model known as 4D. 4D development consists of 4 steps, namely Define, Design, Develop, Disseminat (dissemination). The research subjects of class VII students at SMP N 3 Blora discussing 98 students. Validator The questionnaire was validated by 2 expert lecturers of material, the results of the logical validity test, received 91.25% which means it was in accordance with all aspects. The test instrument was revised according to the validator's suggestion. From the results of tests on students, the results of empirical analysis obtained validity test items were 22 items valid and 8 items were invalid, with a reliability test result of 0.724 which means reliable. Difficulty test results of the test instruments were categorized as 2 difficult items, 24 moderate items and 4 easy questions. While the different power test results obtained 12 bad questions, 15 enough questions, 2 good questions and 1 negative question. Based on the validity test, empirical test instruments that were worthy of re-use were 20 questions, with poor difference but were in accordance with expert lecturers about the material that must be available to represent the material. The level of student literacy in Blora 3 N SMP overall overall is in the sufficient category.